Debt Management Performance Assessment : Ethiopia - World Bank (Washington, DC, 2014)
The DeMPA is a methodology for assessing public debt management performance through a comprehensive set of indicators spanning the full range of government debt management functions. The DeMPA tool presents debt performance indicators along with a scoring methodology. This report pertains to a debt management performance assessment of Ethiopia in 2013, and provides an overview of strengths and weaknesses in government debt management. The following are the significant findings of this assessment: 1) no formal debt management strategy in place, although significant progress has been made over time; 2) there is good coordination and information sharing between the fiscal and monetary authorities and the debt managers; 3) There are documented procedures for external and domestic borrowings as well as for on-lending and loan guarantees; 4) an efficient single treasury account is not yet in place, and surplus cash is invested at low rates; 5) there is an understanding of operational risk but not yet a formal framework for operational risk management; and 6) there are complete and timely debt records for all central government debt and guarantees, with appropriate evaluation and disclosure of information on total central government debt management operations.